Edukasi Digital Safety Dalam Meningkatkan Kecakapan Bermedia Digital Siswa - Herawati, Endang Sri Budi; Mustofa, Zaenal; Sari, Maya Novita; Mirsa, Nur Rina Priyani; Widiyan, Agung Purwa; Astuti, Yuni (Universitas Negeri Gorontalo, 2024)
Digital security plays a crucial role in today's digital era. As the responsible and safe use of the internet becomes increasingly important, encouraging digital security is essential, especially among children and families. By understanding and implementing digital security measures, every individual can reduce the negative impact of digital threats, create a safer and more secure online environment, and protect themselves in the virtual world. Digital safety education aims to provide students with education regarding digital security and tips for keeping personal and parental data secure. The target audience for this program is students at Texmaco Elementary School in grades V and VI. Evaluation of the Digital safety Education program can be measured using questionnaires and tests. Students' thoughts and experiences can be obtained through interviews or group discussions. The results show that the activity received a positive response. Some of the students understood digital safety and how to keep their data secure and controlled. Through digital safety education, it is hoped that students will be able to obtain comprehensive information to prevent themselves from virtual world crimes in the form of personal data hacking.